THE ANALYSIS OF ENGLISH STUDENTS’ PERCEPTION OF MORALE IN ALICE THROUGH THE LOOKING GLASS MOVIE - Diana Lukitasari; Barnabas Sembiring; Indah Damayanti (Journal of English Education and Teaching, 2018)
This research aimed to know the students’ perceptions of morale in “Alice through the looking glass” movie and the influence of morale toward English Students Fourth Semester Class A of Bengkulu University. This research was a Descriptive Quantitative research. In this research, the researcher used questionnaire and interview as the instrument. In the questionnaire the researcher used close-ended and open-ended question. The result showed that the students have good perception about the morale that contained in the movie. That is why there were compatibility between the student’s answer and the researcher analysis. There were 15 morales that the researcher and the students have found. Furthermore, there were some influences of morale to the students such as, students could build a good character, attitude, behavior, and social behavior from it and be able to distinguish what is right and what is wrong.